2019
DOI: 10.1111/jdi.13016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metformin on postprandial plasma triglyceride concentration by administration timing in patients with type 2 diabetes mellitus: A randomized cross‐over pilot study

Abstract: Aims/Introduction Preprandial metformin administration significantly reduces postprandial plasma triglyceride levels in animal studies by reducing intestinal absorption through delayed gastric emptying. However, this effect has not been shown in a clinical study. Therefore, we planned to investigate the efficacy of preprandial metformin administration on postprandial hypertriglyceridemia and the related gastrointestinal effects in patients with type 2 diabetes mellitus. Materials and Methods A total of 11 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
2
12
2
Order By: Relevance
“…Metformin is usually taken before each meal. This common sense was clearly confirmed in a recent study on the efficacy of preprandial metformin administration on postprandial plasma triglyceride concentration in patients with type 2 diabetes. The authors observed that preprandial metformin administration significantly reduced plasma triglyceride levels during meal testing, as compared with no significant reduction in the group with postprandial metformin administration.…”
supporting
confidence: 59%
“…Metformin is usually taken before each meal. This common sense was clearly confirmed in a recent study on the efficacy of preprandial metformin administration on postprandial plasma triglyceride concentration in patients with type 2 diabetes. The authors observed that preprandial metformin administration significantly reduced plasma triglyceride levels during meal testing, as compared with no significant reduction in the group with postprandial metformin administration.…”
supporting
confidence: 59%
“…Less than 2/3 of the clinicians correctly respond to the timing of the drug, according to the drug label ( ® Extended-Releas, 2017 ; ® Tablets and G, 2017 ), which is essential for the drug to reach its optimal glycemic-control effect ( Sato et al, 2019 ). The findings also indicate the potential inappropriate practice of metformin IR use, which call for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin increased fasting GLP-1 in patients with T2D (88,89) potentially by modulating bile acid pools (88). Interestingly, timing of metformin delivery may alter TG responses as pre-meal metformin decreased postprandial TG to a greater extent than post-meal delivery in patients with T2D and increased satiety with no difference in GLP-1 (90).…”
Section: Effects Of Currently Approved Lipid Modifying and Antidiabetmentioning
confidence: 99%